Pengaruh Work Life Balance Dan Lingkungan Kerja Nonfisik Terhadap Kinerja Karyawan Pada PT. Dwipillar Persada Utama Jawa Barat - Riezky Dwinta Sari; Lily Setyawati Kristianti (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study examines the effects of work life balance (X1) and nonphysical work environment (X2) on employee performance (Y) at PT. Dwipillar Persada Utama, Bekasi, West Java. A descriptive quantitative method was employed using saturated sampling of 56 respondents. Data analysis comprised validity and reliability testing, classical assumption tests, regression analysis, correlation analysis, coefficient of determination, and hypothesis testing (t-tests and F-test). Results indicate all instruments are valid and reliable; classical assumptions are satisfied (normality, no multicollinearity, no autocorrelation, and no heteroskedasticity). The multiple regression equation obtained is Y = 0.497 + 0.545X1 + 0.292X2. The simultaneous correlation coefficient is R = 0.903, indicating a very “strong relationship” between the independent variables and the dependent variable, with R² = 0.816. Thus, 81.6% of the variation in employee performance is explained by work life balance and the non-physical work environment, while 18.4% is explained by other factors outside the model. In the multiple model, work life balance has a positive and significant effect on performance (t = 3.350; Sig = 0.001), as does the nonphysical work environment (t = 2.013; Sig = 0.049). Simultaneously, both variables significantly affect performance (F = 117.171; Sig = 0.000). These findings highlight that strengthening work life balance and improving the nonphysical aspects of the work environment are key drivers of employee performance in PT. Dwipillar Persada Utama, Bekasi, West Java.